The Depth Influence to the Morphology and Abundance of Corals at Cemara Kecil Island, Karimunjawa National Park - Suryanti, Suryanti; Supriharyono, Supriharyono; Roslinawati, Yulia (Fakultas Perikanan dan Ilmu Kelautan, Universitas Diponegoro, 2011)
The dominant species of coral depends on environmental conditions or habitat where corals were alive.According to coral life growth, corals have two classification, Acropora and non-Acropora, with different types of morphology branching, massive, encrusting, foliose, tabulate, submassive, mushroom and digitate. Lifeform was influence of some nature factor,one of this factor is depth. The aims of this research were to find and examine the influence of depth on coral morphology, to find abundance of coral, and to find morphology of corals at Pulau Ce mara Kecil, Taman Nasional Karimunjawa. The research was conducted in August until December 2009, in Cemara Kecil Island, Karimunjawa National Park. The research method used was eksplanatif method, sampling method using the line transect method along 20 m. The data gathered were an abundance of corals, reef morphology, coral diversity, and physical-chemical parameters. Research data processed by non-parametric test 2 Independent Samples SPSS 16. The results of this research showed that were not significant difference between corals morphology in depth of 3 m and 10 m.There were 10 species of coral, Acropora Digitate and Acropora Branching species most commonly found at a depth of 3 m, at depth of 10 m most commonly found was submassive coral species. The percentage of live coral abundance range between 52.5% - 79.5%, was generally grouping into well categories until very well. Percentage abundance of the largest reef in the southern part of the depth of 10 m, based on non parametric test 2 independent sam ples showed that it had no significant difference between abundance corals in depth of 3 m and10 m. Keywords: depth, morphology of coral